Dmytro Bilinchuk – "Hmara". Historical Portrait of the Commander of the Ukrainian Insurgent Army in the Territory of Hutsul Region - Понипаляк, О. (Київський національний університет імені Тараса Шевченка, 2020)
The author examined the life military and political activity of Dmytro Bilinchuk, who was the commander of the Ukrainian Insurgent Army (UPA – in Ukrainian) and the leader of the Organization of Ukrainian Nationalists (OUN) on the territory of the Carpathian region of Ukraine during the armed activity of the Ukrainian liberation movement. The researcher studied the history of D. Bilinchuk's service in the "Peremoha" battalion of the Kolomyia Tactical Group of UPA (TV-21 "Hutsulshchyna") and his work in the underground of the OUN. The scientist analyzes the work of D. Bilinchuk in the Security Service of the Organization of Ukrainian Nationalists, his participation in armed actions in the UPA military and combat units against the German and Soviet troops and security forces on the territory of Hutsul region. The author made a study of the Bilinchuk's family investigated the reasons and prerequisites for D. Bilinchuk's accedence to the Ukrainian liberation movement. The scientist used in the research a scientific historiographical base, archival published and unpublished materials from the State Archive of the Security Service of Ukraine in Kyiv. The basis of this scientific work is the Soviet criminal case No. 9866 (contains interrogation protocols of this UPA commander), which was not studied in the context of the study of the biography of D. Bilinchuk. At the same time, in the article the researcher provides biographical information of others UPA commanders and OUN supporters. In general, the author has studied the biography of D. Bilinchuk in the context of the history of the Second World War and the activities of the Ukrainian liberation movement in the middle of the XX century.

Досліджено діяльність Дмитра Білінчука – командира Української повстанської армії (УПА) і керівника Організації українських націоналістів (ОУН) на території Прикарпатського та Карпатського регіонів України в часи збройної активності українського визвольного руху. Висвітлено історію служби Д. Білінчука в курені "Перемога" Коломийського Тактичного відтинку УПА (ТВ-21 "Гуцульщина") та його роботу в підпіллі ОУН. На прикладі розкриття біографії одного із командирів повстанців УПА й керівника підпільників ОУН, здійснено спробу доповнити раніше не розкриті в історіографії теми з історії змагання українського народу за свою свободу в середині ХХ століття.
Дмитро Білінчук-"Хмара" – Історичний портрет командира УПА Гуцульщини
Keywords: Dmytro Bilinchuk; Khmara; OUN; UPA; TV-21 "Hutsulshchyna"; battalion "Peremoha"; Дмитро Білінчук; Хмара; ОУН; УПА; ТВ-21 "Гуцульщина"; курінь "Перемога"